Characterization of thermal infrared medium- and short-term anomaly information from block to fault in mainland China - Zhang, Jingye; Sun, Ke; Du, Chen; Zhu, Junqing (Frontiers in Earth Science, 2023)
The relationship between satellite thermal infrared anomalies and earthquake or fault activity has been studied for more than 30 years. In this paper, for the five strong earthquakes (MS6.1 earthquake in Biru, Tibet; MS7.4 earthquake in Madoi, Qinghai; MS6.0 earthquake in Delingha, Qinghai; MS6.1 earthquake in Lushan, Sichuan; and MS6.8 earthquake in Luding, Sichuan) that occurred in western mainland China in the past two years, the thermal infrared anomaly information features of the block and fault around the earthquake were extracted and analyzed from different temporal and spatial scales using the departure algorithm and the RST algorithm based on monthly MODIS temperature data and daily NOAA satellite longwave radiation data, respectively. The results show that: (1) In the medium-term scale study based on monthly data, all five earthquakes showed relatively obvious anomalous warming in the block near the epicenter in the 1-6 months before the earthquake, and the anomalous warming was obviously controlled by the block tectonics and had a good correspondence with the block location; (2) In the short-term thermal infrared anomaly feature tracking based on daily data, obvious thermal anomalies were also found. The thermal anomalies are concentrated in the three months before the earthquake, and there are multi-day consecutive anomalies. The significant temperature increase generally occurs in a month before the earthquake, and the distribution of the anomalies is mostly in the form of bands, which is basically consistent with the trend of the fault zone. The use of thermal infrared remote sensing data to summarize the dynamic evolution of thermal infrared anomalies of blocks and fault before strong earthquakes can provide a basis for long-term monitoring of fault activity and seismic monitoring by satellite thermal infrared technology.